PENGARUH PROMOSI TERHADAP MINAT BELI KONSUMEN DI ALFAMART BRAGA, JALAN BRAGA NO. 66, KOTA BANDUNG - Kevin Klifford Radja Tumonggor; Paul Eduard Sudjiman (Fakultas Ekonomi Universitas Advent Indonesia, 2022)
This research was conducted to find out how the influence of promotion on consumer buying interest at Alfamart Braga, Jalan Braga No. 66, Bandung City. This study uses a survey method in the form of a questionnaire with a Likert scale, to obtain data. The type of research carried out is verification, with the aim of testing the hypothesis. The author uses a sampling technique that is accidental sampling, and the sample in this study was 99 respondents who visited Alfamart Braga, Jalan Braga No. 66, Bandung City, both consumers who buy or do not buy. The author uses analytical tools, namely validity test, reliability test, F test, simple linear regression analysis and hypothesis testing consisting of t test, coefficient of determination. Based on the results of the study, it can be stated that promotion has a significant influence on consumer buying interest at Alfamart Jalan Braga No. 66 Bandung City.